MICROBES PARAMETERS OF WATER QUALITY FOR AQUACULTURE ON PARI ISLAND WATERS - Lies Indah Sutiknowati (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2013)
The objective of this research was to evaluate waters quality in Pari island waters for aquaculture purpose based on bacteriological information conducted in Mei and September 2011. Microbiological parameters analyzed were total density of bacteria for coliforms, E.coli, pathogenic, heterotrophic, halotoleran, phosphate-nitrate-ammonia breaker, and total cells. Method to analyze coliform bacteria was filtration, identification of pathogenic bacteria using biochemical test, density analises for heterotrophic bacteria, analises for phosphate-nitrate-ammonia breaker bacteria using pour plate, and total cell using Acridine Orange Epifluorescence Microscopy. Results showed that the abundance of total coliform cell was about 1000-7000 colony forming unit (cfu)/100 ml. The abundance of heterotrophic, halotolerant, phosphate-nitrate-ammonia bacteria in seawater was (3.6-4.3)x105 cfu/ml, (1.1-1.3)x105 cfu/ml, (0.5-3.44)x103cfu/ml; and (3.6-6.7)x105 cfu/ml, (1.6-2.7)x105 cfu/ml, (0.6-5.22)x103 cfu/ml in sediment, respectively. The total cell of bacteria was (0.05-2.1)x107cells/ml. The dog-conch (Strombus turturella) and blood-clamps (Anadara granosa) can survive in Pari Island and there was a significant increase in sea grass litter with growth average of 0.67 mm/day and 0.90 mm/day. During snails and clamps growth, there were found several genus of pathogenic bacteria such as Salmonella, Vibrio, Aeromonas, Pseudomonas, Citrobacter, Proteus, Shigella, Hafnia, and Yersinia. The results showed that Pari island waters was suitable for developing shellfish aquaculture dog conch and blood clamps. Keywords: bacteria, parameter, shellfish, aquaculture.